Effect of hope therapy training on life expectancy and general health in cancer patients - Masoumeh Movahedi; Yazdan Movahedi; Ali Farhadi (Journal of Holistic Nursing and Midwifery)
tissues and metastasis. Hopeful spirit is important and essential factor in cancer patients that has many effects on patients adaptability with life situation, especially in periods of pain and suffering. Hope has a significant role on promoting the general health of patient with cancer and affects various steps of disease. Objective: This study aims to determine the effect of hope therapy training on promoting hope to live and general health in patients with cancer. Method: This is an experimental study with pre and posttest with control group. Samples included cancer patients being treated in Shafa Hospital in Ahvaz. They were selected by simple random method. At first, all patients completed the general health and life expectation tests. Then, 30 patients who had the lowest scores in these tests were selected. The training of hope therapy was done in 8 sessions each session lasted 90 minutes. After finishing sessions, posttest was administrated to experimental and control group. Results: Data analysis showed a significant difference in mean scores of control and experimental group (p0.01), so the training of hope therapy leads to improving hope to live and general health in experimental group. Conclusion: In order to improve cancer patients quality of life, presenting educational services and hope promoting program with proper methods such problem based learning or patient active participation can be effective.